Electrostatic risk and specification of field and voltage limits for insulating web materials. (October 2019) - Robinson, Kelly; Smallwood, Jeremy
Abstract: Evaluation of electrostatic risk in production insulating web systems rely on electrostatic field or voltage measurements. Field meter measurement at the centre of a web span gives a direct evaluation of electrostatic risk from net web surface charge density. Surface voltage measured on the web against a grounded conductor can reveal the distribution of charges on each web film surface independently. Considerations for measurement instruments are given.